Social Media Advertising for Achieving Long-term Marketing Objectives - Abashidze, Irakli (European Scientific Journal, ESJ, 2022)
Increasing competition on consumer markets forces businesses to elaborate marketing plans focused on long-term perspectives. This is important in today’s fluctuating and unpredictable business environments, where high level of competitiveness and positive reputation is a premise of survival for a business. Otherwise, it will be unable to retain its share on consumer markets and make plans focused on long-term periods. In this regard, social media advertising is one of the most powerful strategies to reach various marketing goals: brand awareness and high brand value, positive reputation and word of mouth, growing customer base, high ROAS (return on ad spend) in short-term and CLV (customer lifetime value) in the long run. Therefore, it is necessary to research social media advertising in terms of achieving long-term marketing goals. The paper deals with various issues, including advertising opportunities of social media, ways of attracting and retaining customers, raising brand awareness and elaborating strategies focused on long-term results. Discussion provided in the paper is a result of literature review and the author’s observations. Each part of the paper contains recommendatory remarks for achieving long-term marketing goals by using social media advertising strategies. The paper is summarized by a brief conclusion.